Implementasi Etos Kerja Islam Pedagang Muslim Pada Destinasi Wisata Pantai Jumiang - Rusmania, Septi Tri; Faraby, Muhammad Ersya (Universitas Islam Negeri Alauddin Makassar, 2023)
This research discusses the implementation of the Islamic work ethic by Muslim vendors at the Jumiang beach tourist attraction in Pamekasan Regency. This is one of the many reasons why scholars are interested in diving further into the topic of how Muslims in the tourism industry in Pamekasan Regency have incorporated the Islamic work ethic into their operations. In this research a qualitative descriptive approach was used. The research subjects were Muslim tour operators in the Jumiang Beach area. The data used in this research includes primary and secondary data, with secondary data collection carried out through interviews, observation and documentation. Data reduction, data visualization, and drawing conclusions are all steps in the data analysis process. The research was conducted at Jumiang Beach, Tanjung village, Pademawu district, Pamekasan district. The aim of this research is to better understand the implementation of the work ethic of Muslim traders at the Jumiang Beach tourist destination.